Orientation of Preclinical Research in Ovarian Cancer. Issue 8 (October 2017) - Baert, Thaïs; Garg, Abhishek D.; Agostinis, Patrizia; Vergote, Ignace; Coosemans, An
Abstract : Objectives: A large variety of mouse models for cancer exist, also in the field of ovarian cancer. Each model possesses different features, which makes it difficult to interpret their translational value. This review provides an overview of the available ovarian cancer mouse models and their possible use in search for new treatments. Methods: This was a PubMed search of available literature on genetically engineered mouse models, xenografts, transplantable models, and immunocompetent mouse models in ovarian cancer, with a specific focus on clinically relevant features of the described models. Results/Conclusions: Several preclinical models are available for ovarian cancer. Based on their properties, a model should be carefully selected as a function of the experimental setup to achieve clinically relevant results.